DINAMIKA PROKRASTINASI MAHASISWA DALAM PROSES MENULIS SKRIPSI - , Doris Apriani Ritonga, S.Psi, Fathul Himam, Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Studentâs indolence in finishing studentâs final project in universities or writing thesis to gain Bachelor degree caused by procrastination became the researcherâs interest to do this research. Qualitative research by using cases approach about procrastination was done to examine procrastination dynamics done by the students in their thesis writing process. Procrastination discussion was done based on previous research about the definition and dimensionality of procrastination. This research used depth interview toward seven students to collect the data